PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN HASIL PENILAIAN KINERJA GURU TERHADAP KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI KOTA BENGKULU - Syahrul Syahrul (UIN Fatmawati Sukarno Bengkulu, 2020)
Teacher performance is the main Task and function, This is reflected in the appearance, academic ability and the ability of the profession to be a teacher means being able to manage teaching in the classroom and educating students beyond the classroom with the best even the teachers have met the academic level professionalism. But in reality on the ground in general is still a lot of teachers are less effective in carrying out its duties. Therefore, the problem in this research are: Are there academic supervision effect principals on performance of PAI teacher? and Is there PKG results on performance teacher? and Is there an academic supervising principals and PKG results together on the performance of PAI teacher in junior high school in Bengkulu City?, further the objectives of this study are: 1. To explain the academic Supervising Principal Influence on the performance of Islamic education teachers (PAI); 2. To explain the results PKG Effect of PAI teacher against performance teacher; 3. To explain how the implementation of the performance of PAI teachers in junior high school in Bengulu City. This research is a quantitative research that aims to determine the effect of independent variables on the dependent variable. The method used is a survey method, which is to measure symptoms exist without investigating why these symptoms exist, with questionnaires. Research results show that the Supervision of Academic Principal (X1) Positive direct impact on teacher performance (y), amounting to 0.918. or by 91.80%. Further Results Teacher Performance Assessment (X2) has no effect on teacher performance (y) of -307. or by -30.70%. Furthermore Principal Academic Supervision (X1), and the Teacher Performance Assessment (X2) a positive direct impact on teacher performance (y) of 0.845 or 84.50%.